EDAMAME AND OXYTOCIN MASSAGE TO INCREASE BREAST MILK PRODUCTION - Mayangsari, Dewi; Fatmawati, Sri; Rahayu, Hermeksi; Mujahidah, Sa'adah (Jurnal Smart Kebidanan, 2025)
Background: Poor milk production is one of the causes contributing to limited exclusive breastfeeding. Edamame and Oxytocin Massage is a non-pharmacological pain management technique that is anticipated to boost the production of breast milk.Objective: to ascertain the impact of oxytocin and edamame massage on postpartum women's production of breast milk at Karanganyar Health Center. Methods: There is only one group used for the pretest and posttest in this quantitative, pre-experimental study methodology. This study included 32 respondents who were all postpartum mothers on days 2–8 at Puskesmas Karanganyar, Demak Regency, from August 23 to September 3, 2024. Twenty responders made up the research sample. Purposive sampling was the method used for sampling in this investigation. Wilcoxon is used for both univariate and bivariate data analysis.Results: The median amount of breast milk produced at Puskesmas Karanganyar prior to receiving an oxytocin and edamame massage was 22.4 milliliters. The median amount of breast milk produced at Puskesmas Karanganyar following an oxytocin and edamame massage was 41.9 milliliters. At Karanganyar Health Center, postpartum women's breast milk supply is impacted by oxytocin and edamame massage (0.0001 <0.05).Conclusion : At Karanganyar Health Center, postpartum women's breast milk production is impacted by oxytocin massage and edamame feeding. According to the study's findings, midwives can massage postpartum ladies using edamame and oxytocin to boost their supply of breast milk.